Determining the frost tolerance potential of commercially important South African eucalypts - Bahadur, Yakira (My University, 2016)
Currently Eucalyptus plantations in the warm and cool temperate parts of South Africa are being exposed to damaging temperature extremes and unseasonal frost events that, in particular, have detrimental effects on juvenile plantations. To accommodate these conditions, E. grandis and E. nitens have been selected for hybridization in efforts to identify and select clones suitable for successful plantation establishment in affected areas. Biochemical and physiological responses of plants to cold shock and simulated frost conditions offers a means for this type of selection. In this study, the responses of E. grandis, E. nitens and 8 characterized E. grandis x E. nitens (GN) hybrid clones to cold shock and simulated frost conditions were evaluated. The responses elicited were used as an indication of the eucalypts low temperature and frost tolerance potential, based on levels of: reactive oxygen species (ROS), phenolic acids (PA), starch, total soluble sugars (TSS), chlorophyll fluorescence (CF) and relative electrolyte conductance (REC). Plants were subjected to standard growth conditions of 25°C day/14°C night temperature and a 12h photoperiod for 7 days and subsequently cold shocked at 5°C for 24h. Frost conditions were simulated by freezing excised leaf discs from 2°C to -6°C at a rate of -4°C/h with a one hour hold at -6°C. The results showed an upregulation of ROS in E. grandis, GN 1, GN 4 and GN 6, 30-90 minutes into the cold shock; and levels were highest in E. nitens, GN 3 and GN 7 only 24h after the cold shock exposure. PA levels changed marginally under cold shock conditions, with levels of GN 4 increasing the most by 58%. Starch levels of GN 6 were the most affected by the cold shock, where a 33% increase in levels was recorded. TSS levels of E. grandis and GN 6 increased by 201% and 409% respectively, while TSS levels of GN 2 and GN 3 decreased by 41% and 76% respectively. CF levels of E. nitens and two GNs were most affected by the cold shock, however, all the eucalypts tested, except GN 2, GN 3 and GN 6, displayed a high recovery potential to the cold shock. REC levels fluctuated slightly between unfrozen and frozen samples under standard and cold shock conditions and it was found that E. grandis, GN 1 and GN 3 were the least frost tolerant; and GN 4, GN 7 and GN 8 were the most frost tolerant according to REC levels under cold shock and simulated frost conditions. The results indicate that of all the tested eucalypts, only three GNs were not tolerant to the cold shock and E. grandis and two GNs were not tolerant to the simulated frost. Therefore, it was concluded that all of the eucalypts investigated, apart from E. grandis, GN 1 and GN 3, may be suitable for plantation establishment in areas prone to frost in South Africa.
A dissertation submitted to the Faculty of Science, University of the Witwatersrand, Johannesburg, in fulfilment of requirements for the degree of Master of Science. School of Animal, Plant and Environmental Sciences, University of the Witwatersrand, Johannesburg, South Africa. 3 June 2016.
Keywords: Eucalyptus--South Africa